Optimalisasi Operasional Tol Laut dalam Pemenuhan Muatan dalam Palka Kapal Milik PT Meratus Line Surabaya - Nala Inayatuz Zaid; Wahyuni, Okvita; Prasetya, Tri Budi; Hartoyo, Hartoyo (Politeknik Ilmu Pelayaran Semarang, 2025)
The implementation of the sea toll program is carried out by PT Meratus Line as the ship operator. Cargo transportation to Kupang has not been in accordance with the designated slot allocation. This has resulted in inflated Terminal Handling Charges (THC), blank sailings, and complaints from other companies. This study aims to: determine the sea toll load requirements based on Government Regulations, determine the impacts that will occur if sea toll load requirements are not met, and identify strategies for maximizing sea toll load capacity. This study uses a qualitative research method with data collection techniques including observation, interviews, documentation, and literature review. The selected data is then analyzed using the Miles and Huberman theory. The research revealed that the reason for the suboptimal sea toll cargo in the hold was due to the unpreparedness of sea toll cargo and replacement cargo, and a lack of coordination with customers and the terminal. Operations and customer service should recheck and coordinate regarding the condition of the vessel and cargo readiness to avoid empty cargo. Futhermore, the company should provide privileges to customers with fixed shipping schedules.